Oropouche infection a neglected arbovirus in patients with acute febrile illness from the Peruvian coast - Martins-Luna, Johanna (2020)
Objective: To evaluate the frequency of infection caused by the Oropouche virus (OROV) in 496 patients with acute febrile disease (AFI), whose samples were obtained for the analysis of endemic arboviruses in a previous investigation carried out in 2016. Results: OROV was detected in 26.4% (131/496) of serum samples from patients with AFI. Co-infections with Dengue virus (7.3%), Zika virus (1.8%) and Chikungunya (0.2%) were observed. The most common clinical symptoms reported among the patients with OROV infections were headache 85.5% (112/131), myalgia 80.9% (106/131), arthralgia 72.5% (95/131) and loss of appetite 67.9% (89/131). Headache and myalgia were predominant in all age groups. Both OROV infections and co-infections were more frequent in May, June and July corresponding to the dry season of the region.